1999
DOI: 10.1111/j.1439-0426.1999.tb00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery plan for Kootenai River white sturgeon (Acipenser transmontanus)

Abstract: Summary The white sturgeon (Acipenser transmontanus) of the Kootenai River was listed as endangered on September 6, 1994 by the United States Fish and Wildlife Service. This transboundary population, residing in Kootenay Lake and Kootenay River in Canada, and the Kootenai River in the US, has been in general decline since the mid‐1960's. There has been very little recruitment to this population in the last 20 years. This population became isolated from other white sturgeon populations of the Columbia River bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 5 publications
1
94
0
Order By: Relevance
“…Contemporary impacts are primarily dominated by the effects of hydroelectric development and flow regulation in all three river basins [5], with the notable exclusion of the mainstream Fraser where dams are absent. The continued decline of white sturgeon in several spatially isolated populations within these watersheds has led to the species being listed as endangered in Canada [6,7] and the Kootenai River within the Columbia drainage in the United States [8].…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary impacts are primarily dominated by the effects of hydroelectric development and flow regulation in all three river basins [5], with the notable exclusion of the mainstream Fraser where dams are absent. The continued decline of white sturgeon in several spatially isolated populations within these watersheds has led to the species being listed as endangered in Canada [6,7] and the Kootenai River within the Columbia drainage in the United States [8].…”
Section: Introductionmentioning
confidence: 99%
“…The accompanying implementation schedule identifies annually implemented core program elements and the timing and progression of additional measures designed to recover Kootenai River white sturgeon. Efforts to re-establish natural recruitment of Kootenai River white sturgeon initially focused on flows and experimental alteration of Libby Dam operations (USFWS 1996;Duke et al 1999;USFWS 1999). Since 1994, Libby Dam discharges during spring have been augmented and shaped in an ongoing but unsuccessful attempt to stimulate natural recruitment of Kootenai sturgeon.…”
Section: Implementation Planmentioning
confidence: 99%
“…A variety of interrelated factors have clearly contributed to the decline of Kootenai white sturgeon; various hypotheses for recruitment failure are not mutually exclusive (Anders 1991;Anders and Richards 1996;Duke et al 1999;USFWS 1994;1996;1999;Anders et al 2002). Anders et al (2002) suggested that Kootenai River white sturgeon recruitment failure is likely the result of additive mortality from: 1) increased predation efficiencies due to low turbidity, velocity, and an relative increase in predatory fishes, 2) a reduced number of eggs produced by a dwindling spawning population, and 3) spawning in habitat lacking interstitial space (embryo suffocation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few hypotheses that relate the decline in white sturgeons to the change in river hydraulics and sediment transport. Duke et al (1999) outlined a hypothesis that describes how Libby Dam might affect the sturgeon spawning.…”
Section: Introductionmentioning
confidence: 99%